(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Still about wearing the Islamic headscarf and employee discrimination in private undertakings ABSTRACT: This article analyses the development of the jurisprudence of Court of Justice of the European Union on the right to wear an Islamic headscarf at work. In the recent CJEU cases it has been reaffirmed that the employer’s rules do not constitute direct discrimination; however, it has been made clear that a policy of neutrality can justify objectively a difference of treatment indirectly based on religion or belief whether it meets a “genuine need” on the part of the undertaking. This test in most cases is not very different from the one concerning the presence of the “genuine occupational requirements”. The need to seek appropriate forms of composition between the freedom of the worker and the freedom of the company may make anti-discrimination protection under the ground of “religion” weaker than that under the other grounds covered by EU anti-discrimination law; but this is a consequence of the fact that the ground of discrimination constituted by “religion or belief” has been taken by the Court in close connection with the freedom protected by Article 10 EUCFR. SOMMARIO: 1. Premessa introduttiva - 2. Il quadro dei principi di diritto fissati dalla Corte di giustizia in tema di porto del velo islamico nei luoghi di lavoro privato - 3. Il problema dell’individuazione del parametro della “situazione analoga” nel giudizio di comparazione volto ad accertare una discriminazione diretta per motivi religiosi - 4. Alla ricerca delle ragioni in base alle quali si dà per scontata la non praticabilità di una comparazione “esterna” ai dipendenti aziendali di un medesimo datore di lavoro - 5. I termini di una corretta comparazione interna ai dipendenti dell’azienda - 6. L’improponibilità, sul piano sostanziale, di una piena equiparazione del fattore di rischio legato all’esternazione delle convinzioni “religiose” a quello legato all’esternazione di convinzioni “filosofiche” e “politiche” - 7. La presunta migliore adattabilità dello schema della discriminazione indiretta in rapporto a una materia che richiede una peculiare opera di composizione tra distinte libertà fondamentali adeguata alle caratteristiche dell’azienda e alle mansioni svolte dalla lavoratrice - 8. La questione dei limiti di ammissibilità di disposizioni nazionali più favorevoli - 9. Considerazioni conclusive.